PPARG rs3856806 C>T Polymorphism Increased the Risk of Colorectal Cancer: A Case-Control Study in Eastern Chinese Han Population - Lin, Jing; Chen, Yu; Tang, Wei-feng; Liu, Chao; Zhang, Sheng; Guo, Zeng-qing; Chen, Gang; Zheng, Xiong-wei (Frontiers in Oncology, 2019)
Purpose:Functional variants in the peroxisome proliferator‑activated receptor gamma (PPARG) and PPARGco-activator 1 (PPARGC1) family (e.g. PPARGC1A and PPARGC1B) genes were predicted to confer susceptibility to colorectal cancer (CRC).The aim of the present study was to explore the relationship between PPARG polymorphism and the risk of CRC. Patients and methods:we conducted a case-control study with 1,003 CRC cases and 1,303 controls. We selected thePPARG rs3856806 C>T, PPARGC1A rs2970847 C>T, rs8192678 C>T, rs3736265 G>A and PPARGC1B rs7732671 G>C and rs17572019 G>A SNPs to assess the relationship between their variants and risk of CRC. Results: We found that the PPARG rs3856806 C>T polymorphism increased the risk of CRC (TT vs. CC: adjusted OR, 1.59, 95% CI = 1.08–2.35, P = 0.020; TT/CT vs. CC: adjusted OR, 1.26; 95% CI, 1.06-1.49; P = 0.009 and TT vs. CC/CT: adjusted OR, 154; 95% CI, 1.05-2.26; P = 0.028), even after a Bonferroni correction test. The stratified analysis revealed that thePPARG rs3856806 C>T polymorphism also increased the risk of CRC, especially in male, ≥61 years old, never smoking, never drinking, BMI ≥ 24kg/m2, colon cancer and rectum cancer subgroups. Conclusion: Our findings highlight that thePPARG rs3856806 C>Tpolymorphism may increase the risk of CRC. In the futurelarger sample size case-control studies with a detailed functional assessment are needed to further determine the relationship of the PPARG rs3856806 C>Tpolymorphism with CRC risk.